PRELIMINARY STUDY ON BURIAL CHARACTERISTICS OF HARINGEN - Kusmartono, Vida Pervaya Rusianti (Naditira Widya, 2011)
The archaeological remains discovered in a site reflect past human behavior attemptingto adjust oneself with ones surrounding environment. Thus, there should have been a closerelationship between choosing a prospective activity location and humans strategy to fulfill onesbasic needs. Among the sites in the central region of Kalimantan, which indicate the potency todepict the occurrence of a persisting religious-based-tradition of past civilization, is Haringen. Untilnow, one of the traditions which still show the continuity of old culture is burial. In regard to thisresearch, the effort to identify the characteristics of Haringen burial was carried out by using ethnoarchaeologicalapproach. Based on analogical analysis on ethnographic data of the Maanyancommunities who reside in Haringen today, the discussion was foussed on past human behavior inHaringen concerning death management, both involving tangible and intangible features. Therefore,I assume the Haringen burial characteristic is an implementation of the concept of Kaharinganbelief, which is principally, founded from religious concepts occurred in prehistoric period; a periodwhen the concept of ancestor worship was initially developed and elaborated with the concept ofaxis mundi, which is materialized in form of terraced structures.